Two new species of Ocyochterus (Heteroptera: Ochteridae) from Ecuador and Panama - Polhemus, Dan A. (Zootaxa, 2021)
Two new species of Ocyochterus are described, O. graziae from Ecuador, and O. gilloglyi from Panama, and compared to the other two Andean species previously known in the genus. Dorsal habitus and anterior head photos are provided for all described species of Ocyochterus, and photomicrographs are provided for the male genitalic structures of O. graziae and O. gilloglyi. A distribution map is provided for all species in the genus.